Sistem Pengajian Kitab Kuning pada Mahasiswa di Perguruan Tinggi - Mujizatullah Mujizatullah (Al-Ulum, 2018)
This article explains the uniqueness of the educational system of Ma'had Al-Birr of the University of Muhammadiyah Makassar which is studying Kitab Kuning ( a special book for Islamic boarding school). the studying of Kitab Kuning is rarely found at college level. However, the studying of Kitab Kuning is an essential tradition to keep the existence of Islamic institution. It becomes the tool to create young Islamic parsons. Through the good implementation of learning method and strategy, a hundreds of students have been graduated from Ma'had Al-Birr of the University of Muhammadiyah Makassar. their good understanding of Kitab Kuning, they will be an agent of change of Islam society. the studying of KItab Kuning at Ma'had Al-Birr of the University of Muhammadiyah Makassar became the answer of society need of young Islamic parsons who have good skill in speaking Arabic language and also have good understanding of Kitab Kuning.